O conflito social em Maquiavel e a sociedade unidimensional em Herbert Marcuse - Jannarelli, Vicente Cláudio (2011)
The agonistic feature of relity in the Machiavelli s political reflections reveals an intense contrast im relation to the reality identified in the Marcuse s one-dimensional society . If, on one hand, Machiavelli understands the social conflict as being the own cement for the political system stability; Herbert Marcusse, on the other hand, describes, specially in One-Dimensional Man , a kind of society in which happens the weakening and even the disappearance of all radical critique, of all conflict and, as consequence, occurs the integration of all potential opposition in the established system. To present, for reflection, elements resulting from this intense contrast between the Machiavelli s thought on the social conflict and the Marcuse s critical analysis which identifies the disappearance of conflict in the advanced industrial society is the core objective of this present dissertation